2018
DOI: 10.12716/1001.12.01.10
|View full text |Cite
|
Sign up to set email alerts
|

A MCDM Approach with Fuzzy AHP Method for Occupational Accidents on Board

Abstract: Occupational accidents on board criteria determining is a challenging procedure in shipping industry as the ideal safety ship management strategy depends on many factors involving in shipping transportation There are many legislations, agreements and practices to obtain series of security measures in order to ensure safety and security of seafarers. Causes of on-board occupational accidents need to be evaluated in a correct manner to regulate more functional practices and also to lower the on-board accident ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Inadequate safety of ship operations is not only caused by the material precautions but also human factors such as seafarers’ behaviors, habits, lack of attention, and occupational educations [ 12 ]. Most marine accidents are caused by some form of human error as well as incidents [ 13 , 14 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Inadequate safety of ship operations is not only caused by the material precautions but also human factors such as seafarers’ behaviors, habits, lack of attention, and occupational educations [ 12 ]. Most marine accidents are caused by some form of human error as well as incidents [ 13 , 14 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The model uses research methods from the field of decision support systems, mathematical queue theory, statistical analysis, and expert study [25][26][27][28]. These methods were integrated into the computer program generating the results of the study.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the most prominent reason of the accidents is human faults and the most prominent results are economic losses. Likewise, Özdemir et al [13] after determining the factors affecting the health status of seafarers, they analysed these criteria with the Fuzzy Analytic Hierarchy Process (FAHP) method, and it is revealed that the human factor has more effect on the occupational accidents than the others. Nielsen and Panayides [4] approached the occupational accidents in ships with a causal viewpoint and stated that it has been insufficient to focus on the causes of incidents in the previous studies.…”
Section: Introductionmentioning
confidence: 99%